Problem-Based Learning E-LKPD to Improve Learning Outcomes in Pancasila Education - Aren Frima; Tio Gusti Satria (Universitas Pendidikan Ganesha, 2025)
The key to successful learning lies in the availability of appropriate teaching materials, systematically arranged, and functioning as a guide in the learning process to achieve learning objectives. This study aims to describe the results of teacher and student needs analysis, and to test the validity, practicality, and effectiveness of problem-based learning (PBL) in improving learning outcomes of Pancasila Education in fifth-grade elementary school students. This study employs a Research and Development (R&D) approach, utilizing the ADDIE (Analysis, Design, Development, Implementation, Evaluation) model. The research subjects consisted of 40 fifth-grade elementary school students selected through purposive sampling techniques. Data collection techniques included interviews, observations, and learning outcome tests. Data were analyzed quantitatively using descriptive statistics and inferential tests, and supported by qualitative analysis. The results of the study indicate that the Problem-Based Learning-based E-LKPD developed is declared valid, feasible, and effective in improving learning outcomes of Pancasila Education. Media validity is assessed by experts as high to very high on average. Media practicality is assessed by teachers and students as having very practical results. All assessment results indicate that the E-LKPD is highly suitable for use. Effectiveness tests demonstrated a significant improvement in learning outcomes following the use of the E-LKPD. Therefore, the Problem-Based Learning-based E-LKPD is effective in improving learning outcomes in Pancasila Education for fifth-grade elementary school students. The integration of technologies such as Canva Pro and Kvisoft Flipbook Maker represents a learning innovation that can enhance meaningful, enjoyable, and mindful learning experiences.